EVALUASI PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN NOMOR 72 PADA PT. BUMI SELARAS ASRI MANADO - Taminggu, Grace Noviyanti; Kalangi, Lintje; Afandi, Dhullo (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
All companies, whether engaged in trading, services and the real estate industry, must recognize, measure, present and disclose their income in accordance with applicable accounting standards, namely based on Financial Accounting Standards72, so that the information presented in the financial statements is evident and accurate. This research aims to evaluate the implementation of Financial Accounting Standards72 accounting treatment at PT. Bumi Selaras Asri Manado. This type of research is descriptive qualitative research with the aim of describing in writing the data from interviews and documentation. The results obtained indicate that PT. Bumi Selaras Asri Manado in the application of the recognition, measurement, and presentation of its income is in accordance with Financial Accounting Standards Number 72, but in its disclosure it is not fully in accordance with Financial Accounting Standards 72 because the company in its financial statements and notes to financial statements only discloses part of the quantitative information and does not disclose qualitative information. So that there is some information that is not disclosed in the financial statements, such as the separation of revenue based on category that describes how the amount, timing, and uncertainty and cash flows determined by economic factors, and information regarding performance obligations, including information about when the company will recognize sales and information about when payments are due.